Impact of dietary fat levels and fatty acid composition on milk fat synthesis in sows at peak lactation - Li Zhe; Uffe Krogh; Charlotte Lauridsen; Mette Olaf Nielsen; Zhengfeng Fang; Peter Kappel Theil (Journal of Animal Science and Biotechnology, 2023)
Abstract Background Dietary fat is important for energy provision and immune function of lactating sows and their progeny. However, knowledge on the impact of fat on mammary transcription of lipogenic genes, de novo fat synthesis, and milk fatty acid (FA) output is sparse in sows. This study aimed to evaluate impacts of dietary fat levels and FA composition on these traits in sows. Forty second-parity sows (Danish Landrace × Yorkshire) were assigned to 1 of 5 dietary treatments from d 108 of gestation until weaning (d 28 of lactation): low-fat control diet (3% added animal fat); or 1 of 4 high-fat diets with 8% added fat: coconut oil (CO), fish oil (FO), sunflower oil (SO), or 4% octanoic acid plus 4% FO (OFO). Three approaches were taken to estimate de novo milk fat synthesis from glucose and body fat. Results Daily intake of FA was lowest in low-fat sows within fat levels (P < 0.01) and in OFO and FO sows within high-fat diets (P < 0.01). Daily milk outputs of fat, FA, energy, and FA-derived carbon reflected to a large extent the intake of those. On average, estimates for de novo fat synthesis were 82 or 194 g/d from glucose according to method 1 or 2 and 255 g de novo + mobilized FA/d according to method 3. The low-fat diet increased mammary FAS expression (P < 0.05) and de novo fat synthesis (method 1; P = 0.13) within fat levels. The OFO diet increased de novo fat synthesis (method 1; P < 0.05) and numerically upregulated mammary FAS expression compared to the other high-fat diets. Across diets, a daily intake of 440 g digestible FA minimized milk fat originating from glucose and mobilized body fat. Conclusions Sows fed diets with low-fat or octanoic acid, through upregulating FAS expression, increased mammary de novo fat synthesis whereas the milk FA output remained low in sows fed the low-fat diet or high-fat OFO or FO diets, indicating that dietary FA intake, dietary fat level, and body fat mobilization in concert determine de novo fat synthesis, amount and profiles of FA in milk.